Microwave and RF Design Transmission Lines - Steer, Michael (Open textbook library., 2019)
Microwave and RF Design: Transmission Lines builds on the concepts of forward- and backward-traveling waves. Many examples are included of advanced techniques for analyzing and designing transmission line networks with microstrip lines primarily used in design examples. Coupled-lines are an important functional element in microwave circuits, and circuit equivalents of coupled lines are introduced as fundamental building blocks in design. The text and examples introduce the often hidden design requirements of mitigating parasitic effects and eliminating unwanted modes of operation. This book is suitable as both an undergraduate and graduate textbook, as well as a career-long reference book.